2008
DOI: 10.1124/jpet.108.141275
|View full text |Cite
|
Sign up to set email alerts
|

E Series of Prostaglandin Receptor 2-Mediated Activation of Extracellular Signal-Regulated Kinase/Activator Protein-1 Signaling Is Required for the Mitogenic Action of Prostaglandin E2in Esophageal Squamous-Cell Carcinoma

Abstract: The use of nonsteroidal anti-inflammatory drugs is associated with a lower risk for esophageal squamous cell carcinoma, in which overexpression of cyclooxygenase-2 (COX-2) is frequently reported. Prostaglandin E 2 (PGE 2 ), a COX-2-derived eicosanoid, is implicated in the promotion of cancer growth. However, the precise role of PGE 2 in the disease development of esophageal squamous cell carcinoma remains elusive. In this study, we investigated the effect of PGE 2 on the proliferation of cultured esophageal sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 37 publications
(48 reference statements)
3
41
0
2
Order By: Relevance
“…We previously reported that PGE 2 significantly increased the phosphorylation of ERK from 10 to 30 min. 7 In the present study, we found that the mitogen-activated protein kinase (MAPK)/ERK kinase (MEK) inhibitor U0126 at the concentration of 10 nmol/l completely abolished PGE 2 -induced c-Myc expression, suggesting that the protein stability of c-Myc was under the control of ERK pathway (Fig. 3c).…”
Section: Mek Inhibitor Abolished Pge 2 -Induced C-myc Expressionmentioning
confidence: 71%
See 4 more Smart Citations
“…We previously reported that PGE 2 significantly increased the phosphorylation of ERK from 10 to 30 min. 7 In the present study, we found that the mitogen-activated protein kinase (MAPK)/ERK kinase (MEK) inhibitor U0126 at the concentration of 10 nmol/l completely abolished PGE 2 -induced c-Myc expression, suggesting that the protein stability of c-Myc was under the control of ERK pathway (Fig. 3c).…”
Section: Mek Inhibitor Abolished Pge 2 -Induced C-myc Expressionmentioning
confidence: 71%
“…7 Equal amounts of protein (50 lg/lane) were resolved in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and transferred to Hybond C nitrocellulose membranes (GE Healthcare). The membrane was probed with primary antibodies overnight at 4°C and incubated for 1 hr with secondary peroxidase-conjugated antibody at room temperature.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 3 more Smart Citations